Development of a Physics E-Module on Sound Wave Materials Using an Inquiry Approach Based on Scientific Processes - Dhia Kharimah (Journal of Advances in Physics Education, 2025)
This research aims to develop and evaluate the effectiveness of inquiry-based e-modules in teaching the physics of sound waves at SMA Negeri 26 Bandung. The research employs a quantitative R&D approach following the 4D model by Thiagarajan: define, design, develop, and disseminate. Data were collected through concept comprehension tests, questionnaires, and direct observations. Findings show a significant improvement in students' understanding of physics concepts post-implementation of the e-module, with average scores rising from 45.32 to 78.56. Student feedback was positive, with 85% stating the e-module aided their comprehension and 90% finding the learning process more engaging. The study concludes that inquiry-based e-modules are effective in enhancing the quality of physics education and student engagement.